Photometric and Radiometric hoof capsule evaluation in normal and long toeunderrun heel in donkey - El-Marakby , AI; Abdelgalil, AI; Metwally, AA; Mostafa, MB; Soliman, AS (Journal of the Hellenic Veterinary Medical Society, 2024)
There is limited information documenting the normal and long toe-under run heels in donkeys. The objectives of the study were to describe the photometric and radiometric parameters of long toe-under run heel in comparison with normal healthy donkeys in Egypt. Lateral photographs and lateromedial and dorso-palmar radiographs of the fore feet were obtained for both normal and long toe groups. Angular and linear parameters variables were compared between long toe and normal donkeys’ hooves. Morphologically, the toe and heel angles were significantly decreased in long toe-under run heel. The difference between toe and heel angles was higher in normal healthy hooves and decreased in long toe feets. The hoof pastern axis was significantly increased while the hoof base of support showed significant decrease in long toe-under run heel hooves. Radiographically, long toe-under run heels showed significant decrease in the distal phalanx angle, the axis of the distal phalanx angle, the proximal palmar cortex angle and the distal phalanx solar border angle had a negative value. There were no significant variations in the distal phalanx to ground distance, distal phalanx to frog distance, dorsal coronary band height, palmar coronary band height, and heel height index. However, the determined values were consistently less than the healthy hooves. The foot length showed significant decrease and the hoof balance % was significantly increased in long toe hooves. Dorso palmar radiographic parameters of the medial wall length, lateral wall length, lateral coronet to bottom distance, and medial coronet to bottom distance showed no significant difference between normal and long toe-under run heel. The distal phalanx to lateral hoof wall distance had a significant decrease in long toe hooves. This study may help the veterinarians and farriers to take the correct decision for corrective trimming of long toe-under run heel hooves in donkeys.